1998
DOI: 10.1183/09031936.98.11010020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory consequences of sleep apnoea syndrome in patients with massive obesity

Abstract: aaSleep apnoea syndrome (SAS) has been reported to be associated with excess mortality [1,2] and a wide range of cardiac and respiratory sequelae [3][4][5]: daytime alveolar hypoventilation, pulmonary arterial hypertension, systemic arterial hypertension, left ventricular hypertrophy and dysfunction, cardiac arrhythmias and ischaemic heart disease. However, conflicting data have been published on the cardiorespiratory consequences of SAS. This might be due to the fact that most studies did not take sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 23 publications
1
37
1
5
Order By: Relevance
“…The differences in the lifestyle, extreme obesity [7] or genetic predisposition to excessive hypoxic pulmonary vasoconstriction [21] may also contribute to development of PH in some patients with OSAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in the lifestyle, extreme obesity [7] or genetic predisposition to excessive hypoxic pulmonary vasoconstriction [21] may also contribute to development of PH in some patients with OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…Results of majority of studies have suggested that pulmonary hypertension develops in OSAS patients only when signs of COPD are present or they suffer from extreme obesity [3][4][5][6][7]. However, other authors found pulmonary hypertension also in patients with pure OSAS or those patients who are not extremely obese [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of SAS in MO induces greater diurnal hypoxemia [32]. The FRC has shown a negative correlation with the ODI [33]. As for diffusion, an increase in DLCO and KCO has been reported in the obese with SAS, which correlates more with BMI than with SAS itself [35].…”
Section: Resultsmentioning
confidence: 93%
“…Um aumento do volume sangüíneo e do fluxo pulmonar predispõe os indivíduos obesos à hipertensão pulmonar, que pode ser acentuada pela vasoconstrição pulmonar relacionada a alterações pulmonares que causam hipoxemia. A síndrome da apnéia do sono, que está fortemente associada à obesidade, pode acentuar a hipoxemia em certos períodos e agravar a hipertensão pulmonar 16 . Falência cardíaca ocorre com freqüência em pacientes com obesidade grave e parece ser uma importante causa de morte 15 .…”
Section: Alterações Cardiovascularesunclassified
“…Increased blood volume and pulmonary flow predisposes obese individuals to pulmonary hypertension, which may be worsened by pulmonary vasoconstriction related to pulmonary changes which lead to hypoxemia. Sleep apnea syndrome, which is strongly related to obesity, may worsen hypoxemia during certain periods thus aggravating pulmonary hypertension 16 . Heart failure is frequent in severely obese patients and seems to be a major cause of mortality 15 .…”
Section: Cardiovascular Changesmentioning
confidence: 99%